Investigating Global Spatial Patterns of Diarrhea-Related Mortality in Children Under Five - Ali Almasi; Alireza Zangeneh; Arash Ziapour; Shahram Saeidi; Raziyeh Teimouri; Tohid Ahmadi; Mehdi Khezeli; Ghobad Moradi; Moslem Soofi; Yahya Salimi; Nader Rajabi-Gilan; Seyed Ramin Ghasemi; et al. (Frontiers Media S.A., 2022)
ObjectiveInvestigating the trends of child diarrhea-related mortality (DRM) is crucial to tracking and monitoring the progress of its prevention and control efforts worldwide. This study explores the spatial patterns of diarrhea-related mortality in children under five for monitoring and designing effective intervention programs.MethodsThe data used in this study was obtained from the World Health Organization (WHO) public dataset that contained data from 195 countries from the year 2000 to 2017. This dataset contained 13,541,989 DRM cases. The worldwide spatial pattern of DRM was analyzed at the country level utilizing geographic information system (GIS) software. Moran's I, Getis-Ord Gi, Mean center, and Standard Deviational Ellipse (SDE) techniques were used to conduct the spatial analysis.ResultsThe spatial pattern of DRM was clustered all across the world during the study period from 2000 to 2017. The results revealed that Asian and African countries had the highest incidence of DRM worldwide. The findings from the spatial modeling also revealed that the focal point of death from diarrhea was mainly in Asian countries until 2010, and this focus shifted to Africa in 2011.ConclusionDRM is common among children who live in Asia and Africa. These concentrations may also be due to differences in knowledge, attitude, and practices regarding diarrhea. Through GIS analysis, the study was able to map the distribution of DRM in temporal and spatial dimensions and identify the hotspots of DRM across the globe.